Association between HBV, HCV, HIV and ABO Among Blood Donors in Baqubah City, Iraq - Haneen Essam Ali; Areej Atiyah Hussein; Linda Munjed Hadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Blood borne transmitted diseases are a major public health problem worldwide, which has asignificant socioeconomic impact, especially in developing countries.Objectives: To determine the infection rate of hepatitis B virus, hepatitis C virus and human immunodeficiencyvirus among blood donors attended to Blood Bunk in Baqubah City, Diyala, Iraq.Patients and Methods: Cross sectional study which conducted at Blood Bunk in Baqubah City. All datapresented in this paper were collected from blood donors, males 2729 and females 71; they’re aged from17-62 years; during the period from 1st July 2018 till 1st October 2018. Blood samples were collected fromall participants then analyzed by use different enzyme linked immunosorrbent assay (ELISA) kits.Results: High frequency of HBsAg (13.82%) was noticed in this study followed by HCV and HIV 9.25%and 0.61% respectively. Infection in males more than females, and most positive HBV, HIV were in theage group 17-37 years and HCV in age group 38-57 years. Blood group O+ve individuals were commonlyinfected with HBV, 188 (48.58%), HCV 12(52.85%) and HIV, 3(37.5%) as compared with all other bloodgroup donors, followed by another percentage regarding others, blood group B+ve individuals werecommonly infected with HBV 97 (25.07%) after blood group O+ve. Blood group A+ve individuals werecommonly infected with HCV 9 (32.15%) after blood group O+ve. While, HIV is an equal number reportedin A+ve and B+ve blood group individuals. Low percentage was noticed to blood group AB+ve. However,higher number of Rh D positive donors than Rh D negativeConclusions: There were association between viral infections (HBV, HCV, HIV) and blood group of donors,infections with HBV were more than other viruses and common in males and age group (17-37) years.